Top 50 Most-Cited Studies about Osteochondritis Dissecans - Nicholas D. Thomas, M.S; Raegan Mahler, B.S; Kylie Krombholz, B.S; Brendan Williams, M.D; Ted Ganley, M.D; Jeffrey J. Nepple, M.D; Kevin Shea, M.D (Elsevier, 2024)
Purpose: To determine the 50 most frequently cited studies on osteochondritis dissecans (OCD) and to conduct a bibliometric analysis of these studies. Methods: We performed a search within the Clarivate Web of Science database, identifying articles published before December 2022 that encompass topics related to OCD. The search was conducted using the keywords "Osteochondritis Dissecans OR Osteochondritis OR Dissecans."Search results were then filtered using predetermined guidelines and criteria, and the 50 most-cited articles were selected for analysis. Extracted data included title, journal, design, main topic, joint, citations, year, country of origin, and level of evidence. Results: The search yielded 3,865 articles. The 50 most-cited articles were published between 1957 and 2018, with the greatest proportion published from 2000 to 2009 (60%). The most frequently studied topic was treatment (68%), followed by etiology (14%) and imaging (8%). The majority of articles had Level IV evidence (36%) and the largest proportion focused on the knee joint (36%), followed by the ankle (32%), and elbow (6%). The mean citation count per article was 287 (range: 157-1,050), with the most-cited articles primarily published from 2000 to 2003. The leading country of origin was the United States, accounting for 19 publications. Conclusions: Most of the top 50 most-cited articles regarding OCD are about treatment, and the knee is the most-studied joint. The majority of the articles were Level IV evidence and were published in the United States between 2000 and 2009. Clinical Relevance: The top 50 most-cited studies list will provide researchers, medical students, residents, and fellows with a foundational list of the most important and influential academic contributions regarding osteochondritis dissecans (OCD).